Fundamental Error in Capital Asset Pricing Model Theory Beta Gearing and its Demystifying Solution - Garg, Dushyant (Indian Journal of Research in Capital Markets, 2019)
This paper pertained to rectify and improvise the existing means of adjusting beta to debt level of an organization. The value of debt considered for gearing of beta is principal value or interest cost discounted at cost of debt of the same firm. However, this fact needs to be considered whereby two firms whose principal value of debt is same but the interest rate is different, there will be same value of debt considered for gearing. This paper intended to answer the question, if such ignorance of interest rate differential is justified or not, and if not, what is the remedy and correct math to it? This paper intended to provoke the readers to think if interest rate differential is somehow representative of systematic and/or unsystematic risk, and does the existing gearing means considering or ignoring or double counting it. This paper covered the broad and well used area of corporate finance applied in the field of valuation, being CAPM or any other model which uses beta, will have to come across a point where this beta needs to be geared or ungeared either for initial valuation or comparison. Further, the paper is not negatively drafted for the sake of criticism; instead, it majorly focuses towards understanding and remedial action of the problem, leading to a simplified and adaptable solution.